Droplet detachment by air flow for microstructured superhydrophobic surfaces - Hao, Pengfei (Langmuir : the ACS journal of surfaces and colloids, 2013)
Quantitative correlation between critical air velocity and roughness of microstructured surface has still not been established systematically until the present; the dynamics of water droplet detachment by air flow from micropillar-like superhydrophobic surfaces is investigated by combining experiments and simulation comparisons. Experimental evidence demonstrates that the onset of water droplet detachment from horizontal micropillar-like superhydrophobic surfaces under air flow always starts with detachment of the rear contact lines of the droplets from the pillar tops, which exhibits a similar dynamic mechanism for water droplet motion under a gravity field. On the basis of theoretical analysis and numerical simulation, an explicit analytical model is proposed for investigating the detaching mechanism, in which the critical air velocity can be fully determined by several intrinsic parameters: water-solid interface area fraction, droplet volume, and Young's contact angle. This model gives predictions of the critical detachment velocity of air flow that agree well with the experimental measurements